Penanaman Karakter Peserta Didik melalui Peran Budaya Sekolah - Mashuri Mashuri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The Indonesian nation is still experiencing a character crisis in various fields, including in the context of education. The character crisis in the world of education is marked by increased promiscuity, rampant rates of violence against children and adolescents, the habit of cheating, drug abuse, pornography, rape, looting, bullying, brawls, and destruction of other people's property. In fact, this character degradation does not occur in the world of education, because basically the institution is consistently taught science in addition to instilling values in students. To overcome this problem, the government has made various efforts in schools, one of which can be applied through school culture. Through the role of school culture, it is hoped that various characters can be instilled well in students. This study uses a qualitative descriptive approach, which aims to describe a phenomenon as it is. The results show that school culture can instill various characters in students, but must be supported by all school components, especially principals, teachers, and students.